Recent Advancements in Bone Tissue Engineering: Integrating Smart Scaffold Technologies and Bio-Responsive Systems for Enhanced Regeneration - Percival, Kelly M. (2024)
In exploring the challenges of bone repair and regeneration, this review evaluates the potential of bone tissue engineering (BTE) as a viable alternative to traditional methods, such as autografts and allografts. Key developments in biomaterials and scaffold fabrication techniques, such as additive manufacturing and cell and bioactive molecule-laden scaffolds, are discussed, along with the integration of bio-responsive scaffolds, which can respond to physical and chemical stimuli. These advancements collectively aim to mimic the natural microenvironment of bone, thereby enhancing osteogenesis and facilitating the formation of new tissue. Through a comprehensive combination of in vitro and in vivo studies, we scrutinize the biocompatibility, osteoinductivity, and osteoconductivity of these engineered scaffolds, as well as their interactions with critical cellular players in bone healing processes. Findings from scaffold fabrication techniques and bio-responsive scaffolds indicate that incorporating nanostructured materials and bioactive compounds is particularly effective in promoting the recruitment and differentiation of osteoprogenitor cells. The therapeutic potential of these advanced biomaterials in clinical settings is widely recognized and the paper advocates continued research into multi-responsive scaffold systems.